Vocational Skill Interventions Dropout Reduction and Employability - Salam, Jeebanlata (JOURNAL OF INDIAN EDUCATION, 2020)
Dropping out of school mid-way is a serious educational and social problem. By leaving school mid-way, most dropouts have serious educational deficiencies that severely limit their economic and social well-being throughout their adult lives. Many school dropouts find it difficult to secure steady employment and an adequate income. Overtime dropouts face bigger disadvantages because they have fewer opportunities to obtain additional education and training needed to remain relatively relevant and competent in the job market, especially in the context of increased use of new technologies, and changes in the composition of jobs in the economy that will require more educational skills. In the educational hierarchy of school education, India registers disproportionate rate of drop out at secondary level. Significantly, in the educational hierarchy, secondary education is also an important transitory and preparatory stage for school going adolescent youth for preparation of higher education and the world of work. The study is primarily based on reviews of literature on vocational education, dropout reduction or prevention and its effect on employability.